THE POLITICS OF INSECURITY AND FUEL SUBSIDY REMOVAL: THE IMPLICATIONS FOR NIGERIA’S DEVELOPMENT. - Johnson, Marvellous Otega (EBSU Journal of Social Sciences and Humanities, 2024)
This article explores Nigeria’s complex politics surrounding the removal of fuel subsidies and insecurity, with a focus on the significant implications these issues may have on the nation’s development trajectory. Nigeria faces a complex and multifaceted challenges to its development as a result of the ongoing insecurity that is fueled by insurgency, organized crime, and ethno-religious conflicts. This challenges are compounded by the contentious issue of the removal of fuel subsidies. In order to objectively synthesize and analyze recent and past events pertaining to insecurity and the removal of fuel subsidies, as well as to forecast their implications for Nigeria’s development, the historical research design was used in this article. The article’s conclusions indicates among other things, that Nigeria’s development goals are seriously hampered by the politics of insecurity and the elimination of fuel subsidies. In the absence of coordinated efforts to address governance shortcomings, foster social cohesion, and implement fair economic reforms, the nation runs the risk of continuing cycles of instability and underdevelopment. In accordance with the conclusions, the article recommends among other things that the Nigerian government should allot funds/resources to improve security forces’ ability and efficacy in thwarting insurgencies, acts of terrorism, and intergroup violence. In order to better respond to these new threats, this therefore entails enhancing intelligence gathering, supplying security personnel with more advanced weaponry, and training them. It also entails diversifying the economy to lessen reliance on oil income by encouraging non-oil industries like manufacturing, services, and agriculture. To promote economic growth, create jobs, and lower poverty, invest in entrepreneurship initiatives, vocational training, and infrastructure development.